The use of smartphones by university students who work: identifying paradoxes of technology - Corso, Kathiane Benedetti; Moreira, Martiele Gonçalves (Revista de Administração da UFSM, 2019)
With the advent of technology, smartphones have occupied a prominent place in their users’ personal and professional lives. Thus, it is relevant to understand how the relationship between smartphones and individuals occurs, which may be paradoxical and not distinguish the positive and negative uses of the device. This situation may interfere in the lives of these people. This research is a descriptive study, which used univariate descriptive statistical analysis by means of data and Student’s t-test; it was performed with individuals who face double shift (working and studying). We identified the presence of eight paradoxes, which can be classified into two categories: the first refers to the intimate relationship between individuals and smartphones, whereas the second concerns the functionalities of this type of device. This article also retrieves studies that have addressed the theme “paradoxes”, making a comparison with this study. It was possible to notice differences and similarities over the years.